Medical and psychological care for cancer patients at different stages of treatment - Мухаровська, Інна Романівна (ScienceRise: Medical Science, 2017)
Cancer diseases constitute a complex medical, psychological and psychosocial problem. The aim of our research was to identify psychological features of cancer patients at different stages of the treatment and to determine the specifics of medical and psychological care. Contingent and methods. The study was carried out at Kyiv city clinical cancer center during 2014 – 2016. 422 cancer patients attended the survey. 80 of them were at the diagnostic and anticancer treatment choice stage, 187 of respondents were undergoing the primary anticancer therapy, and 155 – re-treatment due to cancer pathology progression. Results. At the different stages of the treatment the need of cancer patients in psychological care were different. That displayed on the preference of forms, conditions, duration and intensity of medical and psychological measures. Psychological care depended on the treatment process stage, treatment type, sex, and the needs of patients. The formation of the positive attitude and availability of psychological interventions as motivating factors was an important practical task. Conclusion. Medical and psychological care in cancer center should be complex, linked to clinical practice tasks, help to recover patients’ mental health, and form an adaptive attitude and effective behavior strategy concerning anticancer treatment